2017
DOI: 10.1155/2017/5937908
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aerobic Exercise Adverse Effects during COPD Exacerbation Hospitalization

Abstract: Introduction. Aerobic exercise performed after hospital discharge for exacerbated COPD patients is already recommended to improve respiratory and skeletal muscle strength, increase tolerance to activity, and reduce the sensation of dyspnea. Previous studies have shown that anaerobic activity can clinically benefit patients hospitalized with exacerbated COPD. However, there is little information on the feasibility and safety of aerobic physical activity performed by patients with exacerbated COPD during hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Although scientific literature is scarce on the feasibility and effectiveness of rehabilitation programs as treatment in hospitalized exacerbated COPD patients, it is believed that rehabilitation can be initiated early during hospitalization [9,10]. However, we did not find other simple aerobic protocols to assess the clinical benefits and any association with systemic inflammation.…”
Section: Introductionmentioning
confidence: 78%
“…Although scientific literature is scarce on the feasibility and effectiveness of rehabilitation programs as treatment in hospitalized exacerbated COPD patients, it is believed that rehabilitation can be initiated early during hospitalization [9,10]. However, we did not find other simple aerobic protocols to assess the clinical benefits and any association with systemic inflammation.…”
Section: Introductionmentioning
confidence: 78%
“…It also reduces the need for endotracheal intubation (42). Numerous studies have shown that patients undergoing regular endurance training are less likely to be hospitalized for acute exacerbation, and even if they require in-patient care, their symptoms are milder and the number of days spent in hospital is lower compared to non-trainees (43)(44)(45). It is well known that not all the patients with COPD are able to perform intense workouts due to dyspnea, fatigue, and rapid exhaustion, and they rather tolerate IT better than continuous exertion (46).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with the literature, we found a reduced distance covered of 38% of the predicted value (230 m) and 43% (268 m) was found in the study of Pitta et al 8 . Another previous study, aimed to evaluate effects of aerobic exercise also find a distance of 224 m 48 h after exacerbation in patients during hospitalization for exacerbation of COPD 36 . Therefore, exercise capacity deserves attention at this moment independently, however with promising association with vascular health.…”
Section: Discussionmentioning
confidence: 99%